Perlakuan Akuntansi Sektor Publik di Desa Sarimekar - Nurul Maghfirah Surianto; Andi Kusumawati; Haliah Haliah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2022)
Theipurpose ofithis study is to analyzeithe procedures for managing financial transactions in Sarimekar Village which are related to the Regulation of the Village Minister, PDTT No. 21 of 2020. This writing is related to the rules for preparing village budget reports. This writing is based on research that describesia symptomior event that is happening at the moment which outlines the concept of the behavior of related officials in Bali. The basis of village transaction orientation tends to be lower than that of local government, but includes all accounts that are already available in local government. Basedion thisiresearch, itican beiconcluded that the accounting principles that have been implemented by the Sarimekar Village administration are in harmony with existing government policies. With the siskeudes (Village Financial Information System) it will prove that the Sarimekar Village government has followed well regarding the presentation and preparation of the APBD Realization Report as contained in the PDDT Village Ministerial Regulation No. 21 of 2020 and village spending allocations are in accordance with Government Regulation no. 43 of 2014.Keywords: PubliciAccounting, AccountingiTreatment Tujuan penelitianiini menganalis tata cara pengelolaan transaksi keuangan di Desa Sarimekar yang berkaitan dengan Peraturan Menteri Desa, PDTT No. 21 Tahun 2020. Penulisan ini terkait kaidah penyusuan pelaporan anggaran desa. Penulisan ini dilandaskan pada penelitian yangimendeskripsikan suatuigejala atau peristiwaiyang terjadi pada saat ini yang menguraikan konsep perilaku pejabat terkait yang ada di Bali. Landasan dari transaksiientitasidesa cenderung lebih rendah dibandingkan dengan pemerintahidaerah, tetapi meliputi semuaiakun yang telah tersedia di pemerintah daerah. Berdasarkan dari penelitianiini dapat ditarik kesimpulan terkait kaidah akuntansiiyang telah di implementasikan olehipemerintahiDesa Sarimekar sudah selaras dengan kebijakan pemerintahan yang telah ada. Dengan adanya siskeudes (sistem Informasi Keuangan Desa) maka akan membuktikan bahwa pemerintah Desa Sarimekar telah mengikuti dengan baik terkait penyajian dan persiapan Laporan Realisasi APBD yang tertuang dalam Peraturan Menteri Desa PDDT No. 21 Tahun 2020 serta alokasi belanja desa telah sesuai dengan Peraturan Pemerintah No. 43 Tahun 2014.KataiKunci : AkuntansiiPublik, PerlakuaniAkuntansi